(3eaJGM ebad GdeYGfi aj Ydei GdHjGf hGdeYGfis - (3CMeO Hf GdeNJGQ Hf Cdejfs
(3ChdgG (B:s
(3hHYO ajbhd CMeO Hf GdeNJGQ MW Gddg Yfg hYf hGdOjg deG JaVd WGdYJ GdCQLhRI , hhbaJ HHGHgG ,` aEPG gi eYWdI GdLjO Hjf CJQGHgG CQOJ Cf GVY YdjgG TQMkG hLjRkG JROgi Hg Ydi cd YRjR s
(3BNQgG (B:s
(3hGdNJe HdaX (B" (3hcedJ (B" (3HQGYI YXjeI , dCf NjQ GdNJe eG cGf HdaXg jDPf HGdNJGe s
(3GdfSNI HgG MhGTs
(3TQM dCQLhRI JHOC H` (B: (3bGd GdabjQ YHGO GdQMef GdMeO ddg Ydi GdHjGf fLR fXegG YGe (B872(3g`s
(3hYOO CHjGJgG Cda HjJ s
(3hGdCQLhRI HGdMeQI s
(3hMhGagG eJbUaI s
(3hGdfSNI eUMMgs
Keywords: (3GdHdGZIs